Drones armados em atividade de segurança pública: limites e possibilidades de regulação - Natália Soares Teixeira Costa (2020)
This work aims to analyze the problem regarding the use of remotely controlled unmanned aerial vehicles, popularly known as drones, armed with lethal or non-lethal weapons, being used in public security activities, especially in police operations, presenting a proposal for the limitation and regulation for such weapons. This research identifies the necessary limits that the Law must impose for the implementation of this new technology, so that no fundamental rights or guarantees are violated. In addition, it questions in which situations it is reasonable and justified to use this type of equipment. Even though there are regulations from ANATEL, ANAC and DECEA that regulate the use of drones, such guidelines are not appropriate to regulate the use of drones by public security agencies. Other norms of the Brazilian legal system also lack an adequate conceptual apparatus to deal with this new technology. Considering this scenario, the matter needs to be regulated based on a provision by a specific law. The use of an armed drone in a police activity will only be lawful if there is at least one officer present at the scene. In the case of a drone equipped with a non-lethal weapon, before using it, the police officer must request authorization from their supervisor; therefore, even without prior authorization, the use will be allowed. However, the use of a drone armed with a lethal weapon will only be legitimate if the police officer obtains permission to use it.